Teaching of English first additional language in rural learning environments: a case for problem-based learning - Malebese, Mots'elisi Lilian; Tlali, Moeketsi Freddie (International journal of inclusive education, 2020)
The teaching of second language that is also a language of teaching and learning of other subjects, has to be meticulous. Considerate attention is utmost where this teaching occurs in under-resourced learning environments where learners encounter the second language for the first time. In instances where the teaching was inadequate, as in the project reported about here, learners performed below expected standards. The project was a one-teacher public primary farm school situated in a remote privately owned land. The school was under-resourced with extremely limited support from the community (farm) and the department of education. The teacher taught all the subjects to the 10 grade 4 learners who were the focus in this project. The project aimed to help improve grade 4 learners' performance in English First Additional Language (second language) on a sustainable basis, by using problem-based learning. The project was framed on underpinnings of socially inclusive teaching strategy and adopted the principles of participatory action research as an approach to generate data. Critical discourse analysis was pivotal for analysing the data. With project-based learning, it was found that learners participated actively in their learning and the ultimate result was learners' performance improvement in English First Additional Language.